Acidification of Residual Manure in Liquid Dairy Manure Storages and Its Effect on Greenhouse Gas Emissions - Sokolov, Vera; VanderZaag, Andrew; Habtewold, Jemaneh; Dunfield, Kari; Tambong, James T.; Wagner-Riddle, Claudia; Venkiteswaran, Jason J.; Gordon, Robert (Frontiers in Sustainable Food Systems, 2020)
Liquid manure storages are an important source of greenhouse gases (GHG) on dairy farms. Methane (CH4) and nitrous oxide (N2O) are the predominant GHGs, while ammonia (NH3) is an indirect source of N2O. Addition of acid to manure has shown promising emission reductions, however, cost of acidification may be unfeasible for farmers. Fully cleaning storages has also shown to reduce CH4, due to removal of inoculating effects of residual manure (“inoculum”) on fresh manure (FM). However, complete removal of inoculum is practically impossible on large farms, thus acidifying only the inoculum may reduce GHGs without requiring acidification of all FM. This study aimed to quantify the effect of acidified inoculum on CH4, N2O, and NH3 emissions from stored manure and quantify the changes in methanogen abundance and activity. Emissions were measured from six 10.6 m3 storages filled with 20% inoculum (1-year-old manure) and 80% FM. Inoculum was treated in three ways: untreated (control); previously acidified (1-year prior); and newly acidified with 70% H2SO4 (1.1 L m−3 manure). The CH4 and N2O emissions were continuously measured from June—November using tunable diode trace gas analyzers coupled with venturi air flow systems. The NH3 emissions were measured at 24-h intervals 3 × weekly using acid traps. The activity and abundance of methanogens were quantified by targeting the Methyl Coenzyme M Reductase A (mcrA) gene and transcript which encodes a subunit of the key enzyme that catalyzes the final step of methanogenesis. Bacterial abundance was quantified by targeting the bacterial 16S rRNA gene. Quantifications were performed using quantitative real-time PCR. CH4 emissions were reduced by 77% using newly acidified inoculum and 38% using previously acidified inoculum, compared to the control with untreated inoculum (36.1 g CH4 m−2). Significant treatment reductions in mcrA gene and transcript abundance suggest that CH4 reductions were caused by disruption of methanogen activity. NH3 and N2O emissions were reduced by 33 and 73% using acidified inoculum and 23 and 50% using previously acidified inoculum, respectively, compared to the control. Results suggest that lower acid rates and acidifying less frequently may still have good treatment effects while minimizing cost.